The DevOps 2.3 Toolkit - Farcic, Viktor; Farcic, Viktor (Packt Publishing, 2018)
Learn from an expert on how to use Kubernetes, the most adopted container orchestration platform.About This BookGet a detailed, hands-on exploration of everything from the basic to the most advanced aspects of KubernetesExplore the tools behind not only the official project but also the third-party add-onsLearn how to create a wide range of tools, including clusters, Role Bindings, and Ingress Resources with default backends, among many applicable, real-word creationsDiscover how to deploy and manage highly available and fault-tolerant applications at scale with zero downtimeWho This Book Is ForThis book is for professionals experienced with Docker, looking to get a detailed overview from the basics to the advanced features of Kubernetes.What You Will LearnLet Viktor show you the wide range of features available in Kubernetes-from the basic to the most advanced featuresLearn how to use the tools not only from the official project but also from the wide range of third-party add-onsUnderstand how to create a pod, how to Scale Bids with Replica Sets, and how to install both Kubectl and MinikubeExplore the meaning of terms such as container scheduler and KubernetesDiscover how to create a local Kubernetes cluster and what to do with itIn DetailBuilding on The DevOps 2.0 Toolkit, The DevOps 2.1 Toolkit: Docker Swarm, and The DevOps 2.2 Toolkit: Self-Sufficient Docker Clusters, Viktor Farcic brings his latest exploration of the DevOps Toolkit as he takes you on a journey to explore the features of Kubernetes.The DevOps 2.3 Toolkit: Kubernetes is a book in the series that helps you build a full DevOps Toolkit. This book in the series looks at Kubernetes, the tool designed to, among other roles, make it easier in the creation and deployment of highly available and fault-tolerant applications at scale, with zero downtime.Within this book, Viktor will cover a wide range of emerging topics, including what exactly Kubernetes is, how to use both first and third-party add-ons for projects, and how to get the skills to be able to call yourself a "Kubernetes ninja."Work with Viktor and dive into the creation and exploration of Kubernetes with a series of hands-on guides.Style and approachReaders join Viktor Farcic as he continues his exploration of DevOps and begins to explore the opportunities presented by Kubernetes.